Two-step cross-linking method for identification of NF-κB gene network by chromatin immunoprecipitation - David E. Nowak; Bing Tian; Allan R. Brasier (BioTechniques)
The chromatin immunoprecipitation (ChIP) assay has recently been exploited as a powerful and versatile technique for probing protein-DNA interactions within the chromatin environment. In this method, intact cells are fixed with a reversible DNA-protein cross-linking agent (formaldehyde), and associated DNA is enriched by immunoprecipitating a target DNA binding protein. The bound DNA in the immune complexes is then used to identify that specific DNA binding protein's endogenous genomic targets. Nuclear factor κB (NF-κB) is a highly inducible transcription factor that controls genetic networks important for pathogen- or cytokine-induced inflammation, immune response, and cellular survival. In our studies of the genetic network under control of the inducible NF- κB transcription factor, we found that the conventional ChIP technique using a single formaldehyde cross-linking step did not reproducibly cross-link it to DNA. As a result, we have developed a novel ChIP assay using a two-step cross-linking procedure, incorporating N-hydroxysuccinimide (NHS)-ester-mediated protein-protein cross-linking prior to conventional DNA-protein cross-linking. We demonstrate that this technique is highly efficient, cross-linking virtually all NF-κB/Rel A into covalent complexes, resulting in quantitative and robust identification of inducible NF-κB family binding to a variety of validated NF-κB-dependent genomic targets. To demonstrate the general utility of this two-step cross-linking procedure, we performed enhanced capture of cytokine-inducible signal transducer and activator of transcription-3 (STAT3) binding to one of its known target genes. Our method represents a significant improvement in the efficiency of ChIP analysis in the study of endogenous targets for rare transcription factors.